ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PADA PT. PLN SANGATTA - Helmi, Awang (EKONOMIA, 2013)
Awang Helmi,factor that influence coNsumer behavior for customer satisfaction of PT.PLN at sangatta under guidance of Mrs.DR.Titin Ruliana,SE,MM and Mrs.Mardiana,SE.MM.            Consideration used byPLN Bontang to open a new Rayon at Sangatta is because the amount of electric power requirement from society and also company,besides the amont of samarinda townee which continue to increase PLN Rayon Upstream samarinda which stand from 2005 with 23.037 customers becomes an atracction because sangatta has the largest amount of townee compared to another city an east berneo province to market this PT.PLN sangatta branch need to now the factors the influence consumer behavior and satisfaction.            The problem are the factors of services,service of goods,and Administration service will have significant effect to PT.PLN sangatta Custumer satisfaction,meanwhile the purpose of this research are to know and analyse consumer behavior,which consisted by services,service of good,and Administration service of PT.PLN Sangatta custumer satisfaction.analysis tool used multiple linear regretion with the help by SPSS version 10.00 program.regretion equation obtained is Y= 2.801+0.153X1 +0.165 X 2 + 0,188 X3 e.            Based on the F test (concurrent test) obtained calculated F= 14.042 > table F = 2.467 so all of free variable have a significant influence to PT.PLN Sangatta branch customer satisfaction supported by R Square coefficient of 0,305 means 30,5 % influenced by the three free variables,and the other 69,5% Influenced by another Factor which not included in this research method. with the t test Obtained the three free variables t calculate>table t means zero hypothesis rejected and probability value of free variables<from alfa 5 % or 0,05 means all free variables are significant.free variable relation (X) namely services variables,service of goods and Administration services to tied variable (Y) is good custumer satisfaction showed by R correlation=0,552 approaching near 1 meanwhile from the consumer behavior factors, administration service have the largest influence to PT.PLN sangatta branch proved by value t calculated=2,554 and the largest standarited cooeficient beta=0,259.            Based on this research showed the services,service of goods,and Administration service have significant influence to customer satisfaction and Administration service factor have the largest influence so the hipothesis accepted.